Behaviour examples for synthesizing automaton models by temporal formulas - Pashchenko, Dmitry V.; Martyshkin, Alexey I.; Trokoz, Dmitry A.; Pashchenko, Tatyana Yu.; Babich, Mikhail Yu.; Butaev, Mikhail M. (Nexo Revista Científica, 2021)
The paper deals with researching and developing the methods that make it possible to account behaviour examples when synthesizing automaton models by temporal formulas. Definitions of the terms and concepts used in work are given; the problem of synthesizing automaton systems according to the specification in the form of temporal formulas and behaviour examples is formulated; a promising algorithm for reducing the problem of synthesizing automaton systems to the Boolean formula satisfiability problem is described; an analysis of the domain and other approaches is carried out. New methods of taking into account behaviour examples in the synthesis of automaton systems according to a specification given in the form of temporal formulas are proposed. Algorithms for constructing graphs of scripts and methods for dividing graphs into clusters are described; they are designed to increase the efficiency of representing behaviour examples used for coding the behaviour examples in the form of Boolean formulas. An experimental study of the proposed methods of accounting for behaviour examples and basic approaches to the presentation of behaviour examples is carried out. The experimental results showed the superiority of the newly developed methods regarding the presentation of scripts in the form of temporal formulas. In summary, the main conclusions of the work carried out are presented.